Analisis Pendapatan Usaha Kacang Garing Pada UD Sari Murni Desa Carangsari, Kecamatan Petang, Kabupaten Badung - MARTA, I MADE ADI; DARMAWAN, DWI PUTRA; SARJANA, I DEWA GEDE RAKA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.5, No.4, Oktober 2016, 2016)
Analysis of Operating Revenues Peanut Crisp at UD Sari Murni Carangsari Village Petang District of Badung Regency Micro, small and medium enterprises in Indonesia is growing very rapidly. Crunchy peanut businesses began to flourish in Badung Regency. The magnitude of the difference between the needs and abilities of the crunchy peanut production is a lucrative business opportunity. One of them is UD Sari Murni. The profit analysis is generally used to evaluate the activity of an industrial business in  a particular period. The purpose of this study was to determine the number and the value of sales of crunchy peanut at UD Sari Murni and its profits earned. The period of data used in this study was the data for one year of 2014.The results of the research showed that UD. Sari Murni is classified as small business, labor-intensive and agriculture-based company. The growth of labor of UD Sari Murni in 2010 through 2014 amounted to 1.25% with an average percentage increase in employment amounted to 21.25%. UD Sari Murni has a vision and mission which are the requirements of a company.There are three processes of the crunchy peanut production cycle at UD Sari Murni, namely: the provision of raw materials, production processes and packaging, as well as crunchy peanut sales process. Patterns of production used by UD Sari Murni were a combination of  constant pattern and fluctuated pattern. Profits earned by UD Sari Murni wasRp.242,096,028.33. But there were still technical obstacles i.e. lack of raw materials, labor shortages, and inadequate processing technology,as well as the presence of obstacles in the social aspect, which is associated with religious ceremonies.
Keywords: profits; crunchy peanuts; sales